Rice protein concentrate as a fish meal substitute in Oreochromis niloticus: Effects on immune response, intestinal cytokines, Aeromonas veronii resistance, and gut microbiota composition. Issue 126 (July 2022) - Reda, Rasha M.; Maricchiolo, Giulia; Quero, Grazia Marina; Basili, Marco; Aarestrup, Frank M.; Pansera, Lidia; Mirto, Simone; Abd El-Fattah, Amir H.; Alagawany, Mahmoud; Abdel Rahman, Afaf N.
Abstract: The potential of rice protein concentrate (RPC) to substitute fishmeal (FM) protein in the diet of Oreochromis niloticus was assessed in a five-month-long feeding trial. Fishmeal protein was replaced by RPC at rates of 0% (control), 25%, 50%, and 75% (RPC0, RPC25, RPC50, and RPC75, respectively). RPC25 had no significant effect on antioxidant capacity (total antioxidant capacity; superoxide dismutase, catalase, and glutathione peroxidase activities) and immune indices (lysozyme, nitric oxide, antiprotease, and bactericidal activities) after one, two, and five months of feeding, while the values for these parameters were significantly lower in the RPC75 group compared to those in the RPC0 group. The RPC25 group showed higher mRNA levels of the intestinal cytokines IL-1β, IL-10β, TGF-β, and TNF-α than the control group. In fish affected by Aeromonas veronii, the highest significant cumulative mortality was recorded in the RPC75 group, followed by the RPC50, RPC25, and control groups. Gut microbiome analyses showed a reduction in microbial diversity in response to the addition of RPC, regardless of the RPC content, and the composition of the community of the RPC samples differed from that of the control. RPC-enriched diets resulted in higher relative abundances of Bacteroidetes and Fusobacteria in the gut compared to that in the gut of the control fish. In summary, RPC can be used to replace up to 25% of the FM protein in the diet of O. niloticus, while improving the antioxidant capacity, immunocompetence, and disease resistance of the fish. Highlights: Partial substitution of fishmeal with plant protein sources improves antioxidant activity till 25% replacement. Intestinal cytokines gene expression was not detrimental affected by fishmeal with plant protein. Cumulative mortality was affected by increase FM especially at 100% replacement.